Extracorporeal membrane oxygenation for failed tPA therapy of pulmonary embolism. (29th February 2016) - Newman, Joshua; Park, David; Manetta, Frank
Background: Pulmonary embolism may cause cardiac arrest secondary to obstruction of blood flow. Traditional treatment strategies include anticoagulation, thrombolysis, and mechanical extraction. Some advocate for support with extra corporeal membrane oxygenation; however, surgical therapies are contraindicated following thrombolytics. Methods: We describe the emergent use of peripheral extra corporeal membrane oxygenation following thrombolytic therapy for a saddle pulmonary embolism associated with multiple episodes of cardiac arrest. Results: The patient was stabilized with peripheral extra corporeal membrane oxygenation, anticoagulated and subsequently weaned from extra corporeal membrane oxygenation without any major bleeding complications. Conclusion: The administration of thrombolytics should not be a contraindication for extra corporeal membrane oxygenation in patients with massive pulmonary embolism associated with hemodynamic instability.